Comparative Analysis of the Best Finsswimmers Strategies in the 800 Meter Surface Monofins at the World Championships - Sidik, Rizky Muhammad Sidik; Fajar, Muhammad Kharis Fajar; Daulay, Dio Alif Airlangga Daulay; Pramono, Bayu Agung Pramono; Nirwansyah, Waristra Tyo Nirwansyah; Bahaudin, Muhammad Arja Bahaudin; Azizah, Nisa Hamidah Nur Azizah; Aini, Aizah Nur Aini (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The use of strategy in competitions is an important aspect in improving an athlete's performance. So it is very important for athletes and coaches to understand this. This research involved 48 finswimming athletes, 24 male athletes, 24 female athletes in the 800 meter surface monofins event at the 2016-2022 World Championships, participants were selected from the best positions 1-8. This research uses secondary data obtained from the CMAS website. The data normality test in this study used Shapirow-wilk. To find out the differences between each round, use the one way ANOVA test. The results of this research show that in the first round, there was a significant time acceleration for female athletes in 2018 with an average time of 24.17 seconds. The time difference between rounds was significant for male athletes in the 2nd to 4th rounds (p < 0.05), while female athletes showed significant time differences in almost all rounds with a value < 0.05. This research concludes that the average male and female athletes in each world championships use a parabola strategy, there is a difference in the average time in each round and there is also a difference in time between male and female athletes